Clinical Nutrition 2013
DOI: 10.1201/b16308-3
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Week Double-Blind Randomized Clinical Trial of Vitamin D3 Supplementation on Body Fat Mass in Healthy Overweight and Obese Women

Abstract: Background: Vitamin D concentrations are linked to body composition indices, particularly body fat mass. Relationships between hypovitaminosis D and obesity, described by both BMI and waist circumference, have been mentioned. We have investigated the effect of a 12-week vitamin D3 supplementation on anthropometric indices in healthy overweight and obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 41 publications
4
73
0
3
Order By: Relevance
“…Intervention studies have been designed to study the causality between low plasma 25(OH)D levels and obesity. Except for Salehpour et al (112) who reported that VD supplementation decreased body fat mass in healthy overweight and obese women, most randomised clinical trials have failed to demonstrate any benefit of VD supplementation in terms of weight loss (113)(114)(115) . These data were recently meta-analysed, and the lack of major effect of VD supplementation on weight loss was confirmed (116) .…”
Section: Effects Of Vitamin D On Obesity and Associated Disorders In mentioning
confidence: 99%
“…Intervention studies have been designed to study the causality between low plasma 25(OH)D levels and obesity. Except for Salehpour et al (112) who reported that VD supplementation decreased body fat mass in healthy overweight and obese women, most randomised clinical trials have failed to demonstrate any benefit of VD supplementation in terms of weight loss (113)(114)(115) . These data were recently meta-analysed, and the lack of major effect of VD supplementation on weight loss was confirmed (116) .…”
Section: Effects Of Vitamin D On Obesity and Associated Disorders In mentioning
confidence: 99%
“…Interestingly, vitamin D supplementation decreases body fat mass without any change in body weight or waist circumference [222]. Further, physical activity and thus sun exposure, which is essential for vitamin D production in the skin [223], decline during menopause [224].…”
Section: Vitamin D Obesity and Menopausementioning
confidence: 99%
“…Other studies, although not weight-loss studies, also found weak relationships between changes in fat mass and 25OHD levels. 12,17 It appears that most studies either observed an increase in 25OHD levels, a pattern where there were greater increases in those that lost more weight or a relationship between the degree of weight loss and increases in 25OHD levels. It may be possible that a threshold of weight loss is needed to see an increase in 25OHD levels.…”
Section: Do 25-hydroxyvitamin D Levels Change With Weight Loss?mentioning
confidence: 99%
“…12 There have also been vitamin D supplementation studies that have reported no changes in weight. [13][14][15][16][17] All studies had significant increases in 25OHD levels following supplementation and found no changes in weight and other measures of body composition in a range of populations. [13][14][15][16] Similarly, Salehpour et al 17 found no differences in weight and waist circumference, but they did find a greater decrease in fat mass in those treated with vitamin D compared with placebo, and this modest reduction in fat mass was inversely correlated with the increase in 25OHD levels (r=-0.32; p=0.005).…”
mentioning
confidence: 99%